CARCINOMA TESTIS PROFILE IN TERTIARY HOSPITAL - Chaerul , Harry Achsan; Seputra, Kurnia Penta; Daryanto, Besut (Indonesian Urological Association, 2023)
Objective: This study was undertaken to estimate the epidemiological characteristics, histological types, and subtypes of testicular neoplasm according to the WHO classification in our patient group. Material & Methods: This was a retrospective study done over a period of ten years from January 2010 - December 2020 in our institution. Histopathological slides were retrieved and reviewed for tumour. Testicular Neoplasm patients who underwent orchidectomy and chemotherapy clinical data including the patient’s age, tumor location, tumor side, pathological finding, tumor marker, chemotherapy regiment, prognosis, chemotherapy response, and side effect were observed. All the data were analyzed descriptively and using SPSS 17.0. Results: A total of 31 cases of testicular and paratesticular neoplasm were encountered in our study with a mean age of 32.516.2 years. The highest incidence was 15-35 years old (48.3). Scrotum mass was the most frequent clinical presentation (70.96%) and left side became the predominant area (52%). Most of the patients come in late stage T3 (51.61%) and N3 (67.74%) with no metastatic process (70.96). The major pathological finding was Seminoma (64.51%), Teratoma (16.12), Yolk Sac (12.9%), Embryonal, and Mixed (3.22%). AFP, B-HCG, and LDH were elevated in some Seminoma, Teratoma, and Yolk Sac groups. The most wide chemotherapy used was 4 series BEP (87.09%). Patient prognosis highest incidence were Intermediate (70.96%). Most of the patients showed complete response (67.74) of chemotherapy. Nausea, vomiting, alopecia, and mucositis were observed as chemotherapy side effect in all patients. Conclusion: Testicular neoplasm peak incidence appears in young male. Most patients come to health care service in late stage. Seminoma become the highest testicular neoplasm incidence in our study. Elevated tumor markers were found in some patients. Four cycle BEP chemotherapy regiment showed great outcome for these patients. Keywords: Epidemiological, histological, testicular neoplasm.